Emergency ultrasound E-FAST (Focused Assessment with Sonography for Trauma) - Segura-Grau, Elena; Segura, Ana; Alba, Margarita; Oviedo, Alberto (Journal of the Portuguese Society of Anesthesiology, 2014)
The Focused Assessment with Sonography for Trauma protocol is defined as the ultrasound detection of free fluid in the pericardial, pleural and intraperitoneal space in patients with blunt abdominal trauma and was expanded in 2004 including the additional diagnosis of pneumothorax. The objective of this paper is to describe the system of this protocol and encourage the use of bedside ultrasound in emergency services. Under current guidelines, the ultrasounds should be integrated in the training of medical emergency plan for what needed proper training programs become to ensure safety and efficacy.